Criminal Sanctions for Robbery a Comparative Study between Fiqh Jinayah and Criminal Law in Indonesia - Munajib, Achmad (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 1 (2021): The 4th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2021)
Humans as social beings deserve to maintain safety and security in life in the world, but acts of terror in the form of robbery crimes still often occur among the community, even though Islam has provided guidance regarding the value of life and property rights over humans. Regarding efforts to prevent and deal with this crime of robbery, the law enforcement agencies of a country have a big responsibility and share in fighting these crimes, making legal provisions designed to protect its people and providing firm sanctions so that the crime of robbery is not free and provides a deterrent effect. The purpose of this study is to examine the handling of robbery perpetrators with criminal sanctions or punishments from the perspective of Islamic law and statutory law in Indonesia, which in this case the limitation used in the Criminal law book (KUHP). This study is library research. The method used is the content analysis which is used to explore the explanations, thoughts, and comments of Muslim scholars. The results of the observations prove that the sanctions for the crime of robbery in fiqh jinayah or Islamic criminal law as described in QS. Al-Maidah [5]: 33, namely: death penalty, crucifixion to death or killed after a long time the perpetrator hung, cut off his hands and feet crosswise, and the last one was exiled from the earth. The sanctions for the crime of robbery as stated in Article 365 of the Criminal law book, namely: 9 years, 12 years, 15 years imprisonment, a maximum prison sentence of 20 years, and the death penalty, or life imprisonment.